Advertisement-financed credit ratings - Heidrun Hoppe-Wewetzer; Christian Siemering (Journal of Economics and Finance, 2021)
This paper investigates the incentives of a credit rating agency (CRA) to generate accurate ratings under an advertisement-based business model. To this end, we study a two-period endogenous reputation model in which a CRA can increase the precision of its ratings by exerting effort. The CRA receives a revenue not from rating fees, as is standard in the literature, but through online advertising. We show that the advertisement-based business model provides sufficient incentives for the CRA to improve the precision of signals at intermediate levels of reputation. Furthermore, we identify conditions under which truthful reporting is incentive compatible.
Keywords: D82; G24; L15; 330; Credit rating agencies; Rating precision; Information acquisition; Advertisement; Reputation